Trends and inducing factors for illicit drug use in Grenada: Epoch 2001 – 2009. - Fagorala, Afolami (Journal of Behavior Therapy And Mental Health, 2016)
Objective The psychosocial aspect of drug use is seldom researched in Caribbean nations. Drug use in the Caribbean has been on the rise since the 1990s. Statistical indicators have established evidence for the increased rates of illegal drug use. This study briefly reviewed these indicators and explored factors that influenced the state of drug affairs in Grenada from 2001 to 2009. Methods Interviews conducted in a semi-structured form were carried out on key stakeholders involved in drug prevention in Grenada. Literary review of pertinent articles from search engines was used to buttress results. Further search through statistical records provided by the Drug Control Secretariat and Grenada Drug Information Network/National Observatory on Drugs (GRENDIN/NOD) was used to obtain information on recent developments surrounding drug related activities in Grenada. Results Trends show marijuana as the drug of choice and males being primarily involved in illegal drug activities. Additionally, cultural, and psychological factors play major roles in the proliferation of the drug problem in Grenada. Conclusion Despite preventive measures used to raise awareness on the dangers of drug use, drug use/abuse/activities are still at an all-time high in Grenada. Focusing on the social, cultural, psychological factors influencing illicit drug activities, and increased cooperation between anti-drug organizations may be effective in curbing illegal drug use in Grenada.
Keywords: Illicit drug use; psychosocial factors; Trends; Drug control; Grenada.